Innovators’ views on involving users and patients in surgical device development: a qualitative interview study - Maroeska M Rovers; Kas Woudstra; Marcia Tummers; Rob Reuzel (BMJ Open)
Objectives Involving end-users and patients in the development of surgical devices, even when patients are not end-users, is deemed important in policy and in academia since it could improve strategic choices in research and development (R&D). Nonetheless, research into innovators’ views on end-user and patient involvement is rare. This study explores what end-users and patients are being involved by innovators during development, what methods for involvement are being used and what topics are being discussed with these end-users and patients.Design A qualitative study featuring semi-structured interviews with innovators of surgical devices. Interviews were recorded and a thematic analysis was performed on verbatim transcripts.Participants 15 interviews were conducted with 19 innovators of 14 surgical devices.Setting Innovation practices of surgical devices in the Netherlands and Belgium.Results End-users were engaged in R&D with formal methods and in unsystematic ways. These users all work in the clinical domain, for example, as surgeons or nurses. The innovators engaged users to analyse problems for which a device could be a solution, define functionalities, make design choices, analyse usability, ensure safety and improve aesthetics. Patients were rarely involved. Innovators stated that patients are not considered to be end-users, that physicians can represent patient interests and that involving patients is unethical as false expectations could be raised.Conclusion Innovators involve end-users with methods and unsystematic ways in the development of surgical devices. Despite governmental calls for patient involvement in the development of medical devices and surgical devices, innovators do not generally involve patients.